TWO FACES OF MASCULINITY IN AXE CHOCOLATE ADVERTISEMENT - Ririn, Bernadeta; Amalia, Lulu Laela (Indonesian Journal of Applied Linguistics, 2012)
Abstract: An advertisement has never been departed from an ideology. Although it occurs implicitly, an ideology in an advertisement is able to make someone believe in particular value of life. This study tries to reveal the ideology both in positive meaning as a belief system which marks certain group and in negative meaning as a false consciousness. Besides that, this study also tries to reveal the way of illustrating the ideology that lies within the Axe Chocolate advertisement. In order to obtain the ideology, each scene in the Axe Chocolate advertisement is analyzed based on Barthes’ model of sign. Then, to find the way of illustrating the ideology, the connotative meaning of mass media codes applied in the advertisement, i.e. fashion codes, color codes, non-verbal codes and technical codes is analyzed. The result of this study shows that masculinity appears as the negative and positive ideology because masculinity is not contradictory with Indonesian culture. However, the value of masculinity shown by the advertiser is narrowed down into the area of sexuality only. In addition to this, the way of illustrating the ideology of masculinity in sexuality area also gives negative stereotype to women, for instance by showing women as figures who like to advertise their body through wearing fashion which exposes women’s body. Keywords: ideology, advertisement, semiotics, mass media codes